Asset growth and the cross section of stock returns - evidence from Vietnam. (2016) - Vo, Xuan Vinh; Bui, Hong Thu
This article sheds light on the question of whether asset growth is a strong candidate for firm stock returns prediction in the emerging market of Vietnam. We test for the asset investment effects in stock returns at the firm level by examining the relationship between the rate of asset growth and subsequent stock returns. We use a large and unique dataset of market and accounting variables of firms listed on the Ho Chi Minh City Stock Exchange for the period from 2008 to 2012. Employing the method similar to Gray and Johnson (2011), our results indicate that asset growth has no significant effect on stock returns in Vietnam stock market. Our results tend to support the findings of Fama and French (2008) but contradict the results of Cooper et al. (2008) and Gray and Johnson (2011) in the context of developed markets.